Production of Clean Energy from Duckweed - Jha, Ajay Kumar; Darlami, Hari Bahadur; Gautam, Rajesh; Pun, Keshab (International Journal on Engineering Technology, 2024)
Duckweed has emerged as a viable and environmentally friendly alternative, demonstrating significant effectiveness in removing organic matter, nitrogen, phosphorus, and heavy metals from wastewater. Its ability to rapidly absorb these pollutants not only makes it an effective wastewater treatment agent but also a valuable feedstock for biogas production due to its high biomass generation. The study has aimed to integrate duckweed cultivation with biogas production, envisioning a more sustainable waste management system and renewable energy source for Nepal. By leveraging the unique characteristics of duckweed, the project seeks to address both wastewater treatment and energy production challenges in a holistic and eco-friendly manner. The research has been meticulously conducted at Pulchowk Campus in Lalitpur, Nepal, with specific sites selected to ensure optimal conditions for both wastewater availability and duckweed growth. The study has utilized artificial ponds established behind the campus canteen and near the girls' hostel, providing controlled environments conducive to duckweed cultivation. The comprehensive methodology employed in the research has included quantitative analysis, an extensive literature review, and the development of mechanisms for biofuel extraction, anaerobic digestion, and bioslurry production. Wastewater samples have been collected and analyzed following established protocols to gauge the effectiveness of the duckweed-based treatment. The growth and performance of duckweed in purifying wastewater have been closely monitored, providing valuable insights into its efficiency and potential for scaling up. Duckweed's rapid growth and efficient nutrient absorption make it highly effective in removing nitrogen and phosphorus, thereby naturally enhancing water quality. Batch B1, serving as the control, uses 100% cow dung, with 6.3 kg of cow dung and no duckweed. Batch B2 consists of 80% cow dung and 20% duckweed, utilizing 5.04 kg of cow dung and 1.26 kg of duckweed. Batch B3 reduces the cow dung to 60%, replacing it with 40% duckweed, containing 3.78 kg of cow dung and 2.52 kg of duckweed. In Batch B4, the ratio is reversed, with 40% cow dung and 60% duckweed, using 2.52 kg of cow dung and 3.78 kg of duckweed. Cumulative biogas yield varied across different batches. Batch B3 (60% cow dung and 40% duckweed) led with 116.64 liters per day, followed by Batch B4 at 56.79 liters per day. The descending order of cumulative biogas yield is as follows: B3 > B4 > B2> B1, indicating that Batch B3 yielded the highest cumulative biogas. Dewatering efficiency steadily improved from pretreatment with sun-drying to post-dewatering, with significant moisture reduction after 48 hours of sun exposure followed by machine dewatering. Lower RPM settings enhanced extraction efficiency, improving the separation of solid cake from liquid and reducing extraction loss from 25.87% at 36 RPM to 22.80% at 8 RPM. This result indicates that lower RPM settings optimize dewatering processes, leading to higher extraction yield, efficiency, and minimized product loss. For biogas production, an anaerobic reactor has been designed and optimized to maximize methane yield using a 50:50 ratio of cow dung and duckweed, reflecting the project's commitment to effective resource utilization. The optimized biogas production, utilizing the 50:50 cow dung and duckweed mixture, has demonstrated the feasibility of integrating waste resources for enhanced energy generation. An efficient dewatering system has been developed, facilitating the transformation of bio-digestate into high-quality bioslurry, which can be used as a valuable agricultural input. Overall, the study has made substantial contributions to improving wastewater management and reducing greenhouse gas emissions by substituting traditional fuels with biogas. It underscores the potential for biogas solutions to address economic and environmental challenges across Nepal, suggesting that broader adoption of such technologies could lead to a cleaner, more sustainable environment and enhanced economic stability.